2018
DOI: 10.1123/ijsnem.2017-0198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2-Weeks Ingestion of High Chlorogenic Acid Coffee on Mood State, Performance, and Postexercise Inflammation and Oxidative Stress: A Randomized, Placebo-Controlled Trial

Abstract: This study measured the influence of 2-weeks ingestion of high chlorogenic acid (CQA) coffee on postexercise inflammation and oxidative stress, with secondary outcomes including performance and mood state. Cyclists (N = 15) were randomized to CQA coffee or placebo (300 ml/day) for 2 weeks, participated in a 50-km cycling time trial, and then crossed over to the opposite condition with a 2-week washout period. Blood samples were collected pre- and postsupplementation, and immediately postexercise. CQA coffee wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 38 publications
1
29
0
2
Order By: Relevance
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies of the level of circulating immune or inflammatory markers have reported small and not consistent variations in relation to habitual coffee consumption [24,25]. Randomized controlled trials of several weeks of coffee consumption in comparison to a water control were also performed and small reductions of some immune/inflammatory mediator concentrations were found, but the opposite was also reported [26][27][28][29][30]. Medium, but not dark roast coffee consumption increased the level of adiponectin [31].…”
Section: Weak Anti-inflammatory Action Of Coffeementioning
confidence: 99%
“…68,69 Farklı formlarda hazırlanmış kahvenin performansa etkilerinin araştırıldığı çalışma örneklerinde Türk usulü hazırlanan kahvenin (3 mg/kg) 5 km performansında artış sağladığı, bunun aksine ise 2 haftalık düzenli Türk kahvesi tüketiminin (474 mg kafein), 50 km bisiklet performansına etkisinin olmadığı da belirtilmiştir. 70,71 Adölesan ve çocuklarda kafein tüketimi artmasına rağmen atletik performansa etkileriyle ilgili araştırmalar nispeten daha azdır. Adölesan ve çocuklarda yüksek doz kafein tüketimi erişkinler-dekine benzer etkilere neden olabileceği gibi, 10-12 yaş kız ve erkek çocuklarda kola ve enerji içeceği gibi yüksek kafein içerikli içeceklerin tüketimi de doz-yanıt ilişkisi çerçevesinde baş ağrısı, iştahsızlık, uyku problemleri ve mide ağrısına neden olabilir.…”
Section: Discussionunclassified